Perempuan Perupa Cina dalam Perubahan Politik di Cina - Ira Adriati Winarno (ITB Journal Publisher, LPPM ITB, 2007)
China has experienced several political changes. The latest change is the emerging of capital-liberalism, which cause their openness to the foreign culture and visitors. This openness has influenced their art work too. The Chinese's Art work is no longer made for propaganda purpose, but shifting to the aspiring of personal expression or for the purpose of social criticism. Yet, seeking the